2019
DOI: 10.1186/s12974-019-1481-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental necrotizing enterocolitis induces neuroinflammation in the neonatal brain

Abstract: Background Necrotizing enterocolitis (NEC) is an inflammatory gastrointestinal disease primarily affecting preterm neonates. Neonates with NEC suffer from a degree of neurodevelopmental delay that is not explained by prematurity alone. There is a need to understand the pathogenesis of neurodevelopmental delay in NEC. In this study, we assessed the macroscopic and microscopic changes that occur to brain cell populations in specific brain regions in a neonatal mouse model of NEC. Moreover, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 81 publications
2
31
1
2
Order By: Relevance
“…Necrotizing enterocolitis (NEC) is one of the many risks of preterm birth. This inflammatory disease of the gastrointestinal tract is a significant cause of neonatal morbidity and mortality 95‐97 . Both neonatal and maternal inflammation appear to contribute to NEC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Necrotizing enterocolitis (NEC) is one of the many risks of preterm birth. This inflammatory disease of the gastrointestinal tract is a significant cause of neonatal morbidity and mortality 95‐97 . Both neonatal and maternal inflammation appear to contribute to NEC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This inflammatory disease of the gastrointestinal tract is a significant cause of neonatal morbidity and mortality. [95][96][97] Both neonatal and maternal inflammation appear to contribute to transcription factor that upregulates production of cytokines and immunological mediators. [98][99][100] In animal models, fetal exposure to maternal inflammation induced by chorioamnionitis has been shown to generate higher levels of inflammatory markers, like IL-6, and reduced intestinal innate immune cells.…”
Section: Ta B L Ementioning
confidence: 99%
“…These results were confirmed by Niño et al , who demonstrated that, in a mouse model of NEC, activation of intestinal TLR4 signalling resulted in the release of high-mobility group Box 1 protein in the intestine, which activated the brain microglia and caused neurological dysfunction 74. More recently, our group reported that the levels of pro-inflammatory cytokines and the density of activated microglia and astrocytes were increased in the brains of mice with NEC and were positively correlated with the increase in the levels of pro-inflammatory cytokines in the gut and the severity of NEC damage, respectively 75. These laboratory findings are useful because they provide an explanation for the development of NEC-associated brain injury by suggesting the activation of the gut–brain axis is implicated in the pathogenesis and are also relevant for their clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental NEC mouse model was established as described previously with a little modification [ 13 ]. In brief, 7-day-old mice were fed by gavage with hyperosmolar formula [Similac Advance infant formula (Abbott Nutrition) and Esbilac canine milk replacer (PetAg) at a ratio of 2:1] every 3 h, meanwhile, exposed to transient hypoxia (5% O 2 , 10 min) and hypothermia twice daily for 4 days.…”
Section: Methodsmentioning
confidence: 99%